2017
DOI: 10.3904/kjim.2016.212
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of connective tissue disease-associated interstitial lung disease: the pulmonologist’s point of view

Abstract: Interstitial lung disease (ILD) occurs in 15% of patients with collagen vascular disease (CVD), referred to as connective tissue disease (CTD). Despite advances in management strategies, ILD continues to be a significant cause of mortality in patients with CVD-associated ILD (CTD-ILD). There is a lack of randomized, clinical trials assessing pharmacological agents for CTD-ILD, except in cases of ILD-associated systemic sclerosis (SSc). This may be due to the lack of CTD cases available, the difficulty of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 86 publications
(95 reference statements)
0
22
0
2
Order By: Relevance
“…Both clinical manifestations, as well as histology of ILD, may vary over a wide range; clinical manifestations can be merely complaint of marginal symptoms or as severe as respiratory failure, similarly, histology can vary from simple inflammation to higher grade fibrosis [27]. Due to the wide ranges of clinical presentation, often with no obvious signs and symptoms and negative pathophysiological examinations, the clinical accuracy is sub-optimal for the diagnosis of ILD associated with CTD [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both clinical manifestations, as well as histology of ILD, may vary over a wide range; clinical manifestations can be merely complaint of marginal symptoms or as severe as respiratory failure, similarly, histology can vary from simple inflammation to higher grade fibrosis [27]. Due to the wide ranges of clinical presentation, often with no obvious signs and symptoms and negative pathophysiological examinations, the clinical accuracy is sub-optimal for the diagnosis of ILD associated with CTD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide ranges of clinical presentation, often with no obvious signs and symptoms and negative pathophysiological examinations, the clinical accuracy is sub-optimal for the diagnosis of ILD associated with CTD [21]. The most common types of pulmonary manifestations in patients with CTD are PAH, NSIP, UIP, desquamative interstitial pneumonia (DIP), organizing pneumonia (OP), and lymphocytic interstitial pneumonia (LIP) [27]. PAH and NSIP were the most commonly observed pulmonary manifestations in our study; the presence of pulmonary manifestation was found to be associated with SLE, MTCD, scleroderma, overlap syndrome, and dermatomyositis, while, it was found to be lesser associated with RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IP occurring within the context of CTD is referred to as CTD-associated IP (CTD-IP) [4,5]. Approximately 15% of ILD patients were diagnosed as CTD-ILD after evaluation [6]. IP can be the primary or sole manifestation of CTD [7], leading to di culties in accurate diagnosis at the rst clinical visit.…”
Section: Introductionmentioning
confidence: 99%
“…However, CTD‐CLD is difficult to manage and is limited by few therapeutic options. Current pharmacologic therapy for CTD‐ILD usually consists of corticosteroids and immunosuppressive agents such as azathioprine, cyclophosphamide or mycophenolate mofetil . However, the effects of these medications are less clear, which suggests a demand for new drugs with better efficacy and tolerability.…”
Section: Introductionmentioning
confidence: 99%